Cervical lymphadenopathy: a clinicopathological study - Guruswamy, Chetas H.; Prabhu, K. Ananth; Basavaraj, H. R. (International Surgery Journal, 2021)
Background: Aim of the study was to evaluate the clinical presentation and histopathological findings in patients presenting with cervical lymphadenopathy. Methods: Patients presenting to the outpatient units and admitted in the wards of departments of general surgery and onco-surgery, Yenepoya medical college hospital, Mangalore from December 2017 to December 2019 were included in the study. Results: From December 2017 to December 2019, 130 patients had presented with cervical lymphadenopathy to our hospital. Cervical lymphadenopathy was most common in the age group of 50-60 years and in males. The most common histopathological diagnosis was found to be secondaries in the neck. Multiple lymph node level involvement was more common. Conclusions: To conclude, cervical lymphadenopathy is seen frequently. In this study conducted in a tertiary centre 130 cases were reported in a span of two years of the study period. Further analysis of age and gender distribution, clinical and histopathological analysis suggested that in majority, age group was found to be above 50 years, with male preponderance. Commonest cause was secondaries in the neck (28.5%) followed by tubercular lymphadenitis (24.6%).